SOCIAL STUDIES STUDENTS' PERSPECTIVES ON THE USE OF THE NATIONAL DIGITAL LIBRARY'S DIGITAL LEARNING RESOURCES AS A SOURCE OF INFORMATION - Muhammad Aprizal; Salsabilla Aulia Putri; Wahyunengsih Wahyunengsih (Kampus Akademik Publiser, 2025)
This study explores the experiences of social studies students in using digital libraries, focusing on accessibility, user satisfaction, content relevance, and technical challenges. Through a mixed-method approach involving questionnaires, interviews, and observations with 50 participants, the research reveals that digital libraries significantly enhance students' academic engagement, information literacy, and research productivity. Most students reported positive experiences in terms of access and interface usability, especially in using Perpusnas (Indonesia’s National Digital Library). However, persistent challenges such as limited full-text availability, slow internet speeds, and the need for improved user guidance continue to hinder optimal usage. The study concludes that addressing technical issues and curating discipline-specific content are vital for improving the efficiency and inclusivity of digital libraries. These findings contribute to the ongoing discourse on digital transformation in education, emphasizing the need for strategic development in digital library services tailored to specific academic fields.